Endothelial and beta cell composite aggregates for improved function of a bioartificial pancreas encapsulation device. Issue 3 (March 2018) - Skrzypek, Katarzyna; Barrera, Yazmin Brito; Groth, Thomas; Stamatialis, Dimitrios
Introduction: Encapsulation of pancreatic islets or beta cells is a promising strategy for treatment of type 1 diabetes by providing an immune isolated environment and allowing for transplantation in a different location than the liver. However, islets used for encapsulation often show lower functionality due to the damaging of islet endothelial cells during the isolation procedure. Factors produced by endothelial cells have great impact on beta cell insulin secretion. Therefore, mutual signaling between endothelial cells and beta cells should be considered for the development of encapsulation systems to achieve high insulin secretion and maintain beta cell viability. Here, we investigate whether co-culture of beta cells with endothelial cells could improve beta cell function within encapsulation devices. Materials and methods: Mouse insulinoma MIN6 cells and human umbilical vein endothelial cells were used for creating composite aggregates on agarose microwell platform. The composite aggregates were encapsulated within flat poly(ether sulfone)/polyvinylpyrrolidone device. Their functionality was assessed by glucose-induced insulin secretion test and compared to non-encapsulated free-floating aggregates. Results: We created composite aggregates of 80–100 µm in diameter, closely mimicking pancreatic islets. Upon glucose stimulation, their insulin secretion is improved in comparison to aggregates consisting of only MIN6 cells. Moreover, the composite aggregates encapsulated within a device secrete more insulin than aggregates consisting of only MIN6 cells. Conclusion: Composite aggregates of MIN6 cells with human umbilical vein endothelial cells have improved insulin secretion in comparison to MIN6 aggregates showing that the interaction of beta cell and endothelial cell is crucial for a functional encapsulation system.